+0  
 
+1
123
1
avatar+1015 

Solve the system of equations using the substitution method.

AngelRay  Mar 4, 2018
 #1
avatar+12650 
+1

Since you have the definition of 'y' in the first equation  2+1/4x   let's substitute THAT  for 'y' in to the second equation

 

3x - 5 (2+1/4x)  = -3     then solve for x

3x - 10 - 5/4  x  = -3

3x-5/4 x = 7

7/4 x = 7

x = 4              Now sustitute this value of 'x' into one of the two equations to find 'y'

 

3(4) - 5y = -3

12 -5y + -3

-5y = -15

y = 3

ElectricPavlov  Mar 4, 2018

46 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.